Creative economy and culture challenges, changes and futures for the creative industries - Hartley, John 1948-; Li, Henry Siling; Wen, Wen (Lecturer in cultural industries) (Sage, 2015)
Creative Industries studies is now well-established in higher education in many countries, especially in universities and colleges where there is a component of creative-practice education as well as cultural and aesthetic theory or business and economic analysis. The Creative Industries field is an interdisciplinary amalgam that draws from the humanities, the creative arts, technology studies, and the social sciences. Cultural, economic, political, artistic, scientific and technological discourses all contribute to the Creative Industries, and all deploy their own specialist language. This book shows how a coherent field is slowly resolving itself into focus through this diverse, distributed, multi-discursive and undirected collective enterprise. It charts a pathway through the terrain, showing how students, researchers, entrepreneurs, practitioners and policymakers can make use of recent advances in the systematic study of the creative process on a population-wide scale.